Who is in, for How Long and What for. Exploring the Social Dimension of Cannabis Social Clubs in Barcelona, 2017-2020 - Obradors-Pineda, Anna (Journal of drug issues, 2025)
Analyzing the activity data of 2007 Cannabis Social Clubs (CSCs) members in Barcelona between 2017 and 2020 we describe the demographics, the amounts of cannabis collected (.46 g/day amongst men; .37 for woman) and the relationships established with the CSCs: frequency of procurement (every 15.4 days for woman; 11.6 days for men); and membership length (mean 657.3 days). An 80% of members were men (mean 36.1 years old). Women, older adults, and those registered as medical users had generally longer memberships than the average despite the frequencies and the amounts procured by them tended to be lower compared to young recreational male members. The daily amount used rose from an estimated general average of .44 g, to an estimated 1.41–4.76 g collected by a 5% of CSC members. Beyond providing small amounts of cannabis, CSCs are mainly used as socializing spaces for people who use cannabis.